LA NUMÈRIQUE DANS LES CLASSES DE FLE («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article talks about the use of digital technologies in learning French and the role of digital technologies in language learning.
Keywords: Foreign language, Digital technologies, computer, tablet, smartphone, science, mass media.